Effects of Video Modeling on Gymnastics Routine Performance - Ching, Joo Lan (2006)
Modeling or observation learning plays an important role in transmitting information to the observer. Some sport skills such as skills in artistic gymnastics need explicit visual demonstration for the purpose of coaching and training. Hence, videotapes are sometimes used to facilitate the learning process. However, there is limited agreement from previous studies on the effectiveness of video modeling. The purpose of this study is to investigate the effects of video modeling versus non-video modeling on routine performance of female gymnasts who participated in a gymnastics development program managed by National Sports Council of Malaysia. Twenty- four subjects between the ages of 8 to 15 years (M = 11.13, SD = 2.08) from a group of 67 gymnasts were chosen at random from the gymnastics centers around Malaysia. The subjects in each center were matched and randomly assigned to either the video modeling (experimental) group or the non- video modeling (control) group. Both the experimental and control groups attended their normal gymnastics training program. The experimental group was given the opportunity to watch 15 hours of video clippings in three sessions of half an hour per week over a 10-week period while the control group attended gymnastics training only. The video modeling sessions comprised of female gymnasts participating in the Olympic Games (Sydney), Commonwealth Games (Manchester), World Championships (Ghent), and other international championships. The researcher videotaped pretest and posttest performance of each gymnast on the two gymnastics events at each center. Subsequently, two top Malaysian women's judges evaluated the 192 routines performance recorded (24 subjects x 2 rotations x 2 events x 2 tests) according to the Federation Internationale de Gymnastique (FIG) rules.